Risk Factors of Recurrent Anal Abscess in Patients with Type 2 Diabetes Mellitus; a 4-Year Retrospective study - Malekpour Alamdari , Nasser; Afaghi, Siamak; Esmaeili Tarki , Farzad; Fathi, Mohammad; Besharat , Sara; Rahimi, Fatamehsadat (Archives of Academic Emergency Medicine, 2022)
Introduction: Anal abscess is considered as a relatively common compilation in type 2 diabetes mellitus (T2DM) patients. This study aimed to determine the risk factors of recurrent anal abscess in T2DM patients. Methods: In this 4-year retrospective cross-sectional study, T2DM patients hospitalized due to anal abscess in Shahid Modarres Hospital, Tehran, Iran from December 2016 to December 2020 were studied. The independent risk factors of disease recurrence were determined among demographic factors, underlying diseases, diabetes-related factors, clinical factors, laboratory parameters, abscess type, and culture using multivariate stepwise logistic regression analysis. Results: 203 patients were enrolled in the study. 58 (28.6%) patients had at least one re-occurrence of anal abscess during four years. The recurrent episodes had occurred more frequently in the first year after the initial treatment (55.2%). The prevalence of comorbidities such as metabolic syndrome, coronary artery disease, chronic kidney disease, end stage renal disease, and peripheral vascular disease was significantly higher amongst patients with abscess recurrence. The patients with recurrent anal abscess had statically significant poor glycemic control (HbA1C > 7.5), decreased levels of Estimated Glomerular Filtration Rate (e-GFR), and higher C-reactive Protein (CRP) upon the first admission. Presence of metabolic syndrome, HbA1c > 7.5%, WBC > 11.0 ×109/L, and CRP > 5 mg/l were amongst the independent risk factors of recurrence. HbA1c > 7.5% was the greatest independent risk factor of anal abscess recurrence (OR=2.68, 95% CI: 1.37-5.25; p < 0.001). The area under the receiver operating characteristic (ROC) curve (AUC) of HbA1C, CRP, and WBC in predicting the risk of abscess recurrence was 0.81, 0.71, and 0.64, respectively. Conclusion: Th recurrence rate of anal abscess in this series was 28.6 %. It seems that in T2DM patients with uncontrolled diabetes who have metabolic syndrome and increased CRP and WBC in their routine tests, the probability of anal abscess reoccurrence is high.